PERAN BIROKRASI LOKAL DALAM SKEMA PENGELOLAAN BERSAMA SUMBER DAYA AIR - Hanantyo Sri Nugroho (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Bureaucratic capacity in controlling the public-private partnership scheme is inadequate, so that the scheme does not protect the public interest. This paper uses the perspective of institutional approach to the market based government to help explain menggejalanya unpreparedness of government bureaucracy when it should be involved in the scheme of privatization policy in the management of shared water resources. This perspective requires the organizers to run the country together with a logic state power market participants. It is important to note that, in her involvement in politics and the logic of the market running, simultaneously also ongoing political interaction. Therefore, bureaucracy as the parties involved in the privatization scheme is important to analyze the attitude, position and political struggles.